Numb and Alzheimer’s Disease: The Current Picture - Ntelios, Dimitrios; Berninger, Benedikt; Tzimagiorgis, Georgios (Frontiers in Neuroscience, 2012)
Twenty three years ago, numb was identified as a critical regulator in Drosophila sensory organ precursor cell asymmetric divisions. Beyond the recently recognized role in carcinogenesis, Numb seems to be important in Alzheimer’s disease. This assertion comes from the involvement in various processes such as synapse morphogenesis, APP trafficking, notch signaling and neurogenesis. The purpose of the present mini-review is to provide the current picture of Numb’s participation in mechanisms underlying Alzheimer’s disease pathogenesis and emphasize potential aspects for future research.